2014
DOI: 10.1021/am5011628
|View full text |Cite
|
Sign up to set email alerts
|

Water-Stable, Adaptive, and Electroactive Supramolecular Ionic Material and Its Application in Biosensing

Abstract: Developing water-stable and adaptive supramolecular materials is of great importance in various research fields. Here, we demonstrate a new kind of water-stable, adaptive, and electroactive supramolecular ionic materials (SIM) that is formed from the aqueous solutions of imidazolium-based dication and dianionic dye (i.e., 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), ABTS) through ionic self-assembly. The formed SIM not only shows good thermostability and unique optical and electrochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…According to our earlier work, the SIM was synthesized by mixing an aqueous solution of the hydroxide-exchanged form of C 10 (mim) 2 (2 mM) with an equal amount of ABTS (2 mM) under stirring for 2 h at room temperature to produce a white precipitate. The precipitate was washed several times with doubly distilled water, collected by centrifugation, and dried in a vacuum drying oven.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our earlier work, the SIM was synthesized by mixing an aqueous solution of the hydroxide-exchanged form of C 10 (mim) 2 (2 mM) with an equal amount of ABTS (2 mM) under stirring for 2 h at room temperature to produce a white precipitate. The precipitate was washed several times with doubly distilled water, collected by centrifugation, and dried in a vacuum drying oven.…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by this need, we are interested in preparing water-stable supramolecular ionic materials by ionic self-assembly from an aqueous medium. Our previous attempts have revealed that water-stable supramolecular ionic materials (SIMs) based on an imidazolium-based dication (e.g., 1,10-bis­(3-methylimidazolium-1-yl) decane, C 10 (mim) 2 ) and electroactive dianionic (e.g., 2,2′-azino-bis­(3-ethylbenzothiazoline-6-sulfonic acid), ABTS) with good water stability, adaptive encapsulation capability and solvent stimuli-responsive properties can be prepared . Interestingly, herein, we find that solid-state supramolecular materials created via ionic self-assembly show humidity-dependent conductivity.…”
mentioning
confidence: 99%
“…10A). 46,47 The formed SIMs not only show good thermostability and unique optical/electrochemical properties that are originated from the precursors of the SIM, but also exhibit good water-stability, salt-stability, and adaptive encapsulation properties toward some heterocyclic cationic dye molecules. These unique properties essentially made the materials particularly attractive for chem/(bio)sensor development.…”
Section: Interionic Interaction For Sensing Materials Preparationmentioning
confidence: 99%
“…For example, by encapsulating electroactive molecules (e.g., methylene green, MG) into the materials through the interionic interaction between MG and the anionic building blocker (i.e., ABTS), an electrochemical sensor for NADH was developed at a low potential of À0.07 V (vs. Ag/AgCl). 46 Again, by encapsulating optically active rhodamine 6G into the materials, a visualization assay was successfully established for on-the-spot and fast sensing of alcohol using thin-layer chromatography. 48 As shown in Fig.…”
Section: Interionic Interaction For Sensing Materials Preparationmentioning
confidence: 99%
“…In biosensor development, this characteristic can be of great importance [48]. Recently, Zhang et al [49] reported a biosensor based on an adaptive material composed by an electro-active supramolecular ionic material of imidazolium di-cation and di-anionic dyes. These compounds self-assemble, resulting in a structure with unique optical and electrochemical properties and adaptive encapsulation properties in the presence of cationic dyes.…”
Section: Supramolecular Compounds For Optical Biosensorsmentioning
confidence: 99%